CHRONOAMPEROMETRY AT CHANNEL ELECTRODES - EXPERIMENTAL APPLICATIONS OF DOUBLE ELECTRODES - Compton, R; Coles, B; Gooding, J; Fisher, A; Cox, T (1994)
Applications of transient experiments using double-channel electrodes are reported. The current response of a downstream detector electrode to a potential step at an upstream generator electrode is found to be in good agreement with theory. Such experiments are used to (i) demonstrate that the diffusion coefficient of the electrogenerated radical anion of p-chloranil in acetonitrile solution is 0.94 × 10-5 cm2 s-1, which contrasts markedly with that of the parent material (1.75 × 10-5 cm2 S-1), and (ii) characterize the nature of electrolytic processes occurring at the surface of porous silicon electrodes. The latter are shown to be electroactive throughout the depth of the porous surface layer. © 1994 American Chemical Society.